Analisis Peran Lembaga Swadaya Masyarakat (LSM) dalam Advokasi Hak Asasi Manusia di Indonesia - Siti Nur Azizah; Andi Pratama (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2026)
Non-governmental organizations (NGOs) play a crucial role in human rights advocacy in Indonesia, particularly in fostering public awareness and influencing government policies related to the fundamental rights of citizens. This study aims to analyze the contribution of NGOs in fighting for human rights in Indonesia, focusing on their efforts to promote the protection, advancement, and enforcement of human rights. The approach used in this study is qualitative, employing literature review and in-depth interviews with NGO representatives, human rights activists, and other relevant parties. The research findings indicate that NGOs play a strategic role in advocating for human rights issues, whether through public education, public campaigns, or litigation in court. NGOs also serve as partners to the government and international institutions in introducing and implementing international human rights standards in Indonesia. Although their contributions are significant, NGOs also face various challenges, including political pressure, restrictions on freedom of expression, and a lack of government support. This study concludes that NGOs must continue to strengthen collaborative networks with various stakeholders to enhance their influence in human rights advocacy in Indonesia.